PENGETAHUAN GIZI, AKTIVITAS FISIK, KONSUMSI SNACK DAN PANGAN LAINNYA PADA MURID SEKOLAH DASAR DI BOGOR YANG BERSTATUS GIZI NORMAL DAN GEMUK - Deni Deni; Cesilia Meti Dwiriani (Food and Nutrition Society of Indonesia, 2009)
Childhood obesity is increases rapidly in developing country. It’s has important short-term and long-term medical consequences also psychosocial consequences. The objective of the research is to analyze nutritional knowledge, physical activity, snack habit, in normal and overweight of Bina Insani elementary students in Bogor. The cross sectional study design was used in this study to analyze nutritional knowledge, snack habit, and physical activity in normal and overweight students. The total number of 80 students sample was chosen randomly. It consists of 40 students sample with normal nutritional status and 40 students sample with overweight nutritional status. Primary data consisted of physical activity recall (1x24 hours), food consumption recall (2x24 hours), anthropometry data (weight and height), social-economy’s sample condition, food habit, and snack habit using Food Frequency Questionnaire (FFQ). Secondary data were included data of Bina Insani Elementary School. The result showed no relation between level education and wage of parent, nutritional knowledge level, nutritional attitude, snack habit and physical activity with nutritional status of sample. The average energy adequacy level according to WNPG (2004) respectively 82.2% in normal sample and 73.6% in overweight sample.